Answer :
Answer:
[tex] (x+1)^2 + (y-1)^2 = 16[/tex]
And the general formula for a circle is given by this expression:
[tex] (x-h)^2 +(y-k)^2 = r^2[/tex]
With the center (h,k) and the radius r. If we compare this general expression with the formula that we obtain in (1) we see that :
[tex] h = -1, k =1 , r =4[/tex]
So then the best solution for this cae would be:
b. center: (-1,1)
radius =4
Step-by-step explanation:
For this case we have the following equation given:
[tex] x^2 +2x + y^2 -2y -14=0[/tex]
And we can complete the squares for this case like this:
[tex] x^2 +2x +(2/2)^2 +y^2 -2y +(2/2)^2 =14 +1+1[/tex]
[tex] (x^2 +2x +1) +(y^2 -2y +1) =16[/tex]
Now we can rewrite the last expression like this:
[tex] (x+1)^2 + (y-1)^2 = 16[/tex]
And the general formula for a circle is given by this expression:
[tex] (x-h)^2 +(y-k)^2 = r^2[/tex]
With the center (h,k) and the radius r. If we compare this general expression with the formula that we obtain in (1) we see that :
[tex] h = -1, k =1 , r =4[/tex]
So then the best solution for this cae would be:
b. center: (-1,1)
radius =4